EFEKTIFITAS POSKESTREN DIGITAL TERHADAP PENCEGAHAN PERILAKU SEKS PRANIKAH PADA REMAJA - Bariana Widitia Astuti; Setyowati, Rustiana; Anggoro, Sarni (Biro Akademik, Penelitian dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2025)
Technology is one of the factors influencing adolescent premarital sexual behavior. Technology makes it easier for adolescents to obtain information about sexuality through various sources. Rapid technological developments in recent years have encouraged the emergence of various innovative health promotion media for adolescent reproductive health based on applications. This media provides opportunities for students to learn independently to improve their understanding of reproductive health. This study aims to determine the effectiveness of digital health posts (poskestren) in preventing premarital sexual behavior in adolescents. The research design used a quantitative quasi-experimental design with a one-group pre- and post-test design. This study was conducted from May to June 2025 at MAN 4 Bantul. The subjects were 142 first- and second-grade students residing in Islamic boarding schools. This study used a purposive sampling technique in selecting respondents. Data analysis began with a normality test using the Kolmogorov-Smirnov test, which showed that the data had a normal distribution. Next, statistical testing was carried out using a paired t-test. The study results showed significant behavioral differences in students following a four-week intervention using digital health education posts (Posketren). There was a significant difference between levels of reproductive health knowledge before and after the health education intervention using digital health education posts. This demonstrates that digital health education posts are significantly effective in preventing premarital sexual behavior in adolescents.